A framework for integration of digital product presentations for enhancing market share in Indian MSME’’’’s. - Krishnamurthy KB; Kumar S, Dr. Mohan; Chittaranjan, Dr. Prashanth; Yadwad, Dr. Aravindrao.M.; Patil, Dr. Hema (The journal of contemporary issues in business and government, 2019)
With a tremendous growth in e-commerce, digital product presentation (DPP) has gained widespread popularity, due to the number of advantages offered such as display options, 3D views, video, and audio, etc. The present study aimed to assess the impact of DPP on consumer buying decisions and satisfaction, along with the challenges faced by MSMEs in using DPP. This study was conducted a survey of 124 consumers of different products that are marketed using DPP technology. Moreover, interviews were carried out with five MSMEs marketing representatives that use DPP for marketing of their products. The results indicated that digital product presentation have a significant impact on consumer buying decisions and satisfaction due to advantages such as enjoyable shopping experience, easy availability of product information and a simpler decision-making process.